Local Barycenter Based Efficient Tree-Support Generation for 3D Printing. (October 2019) - Zhang, Nan; Zhang, Li-Chao; Chen, Ying; Shi, Yu-Sheng
Abstract: 3D printing technology that enables fabrication of custom objects for home users has become popular in recent years. However, additional support structures have to be generated to support the overhanging models. As the critical step of 3D printing, the support generation technique plays an important role in 3D printing software in engineering applications. In this paper, a new Local Barycenter based Tree Support (LBTS) algorithm is developed with good property of higher efficiency and less material using to generate support structures for overhang regions acquired from the mesh solid. Based on a divide and conquer strategy, supporting points generated from an overhang region can be divided into sub-regions iteratively. In each sub-region, a new tree node is calculated based on the local barycenter of children nodes, then new tree pillars are created. Based on the constructed tree topology, variable diameters of tree nodes are calculated to ensure the tree stability during the printing. Moreover, with regard to the interference search, which is an inevitable and extraordinarily time-consuming process in conventional support approaches, an efficient interference search algorithm with constant time complexity is developed based on the proposed Double-Voxel based Interference Search Tool (DVIST). Experimental results show that the proposed LBTS approach outperforms the previous methods in algorithm execution efficiency and support structure material saving. Graphical abstract: Highlights: Build tree-support structures efficiently based on a divide and conquer strategy. A fast solution for interference search to accelerate the support generation. Create new tree-node with variable diameters via local barycenter of children nodes.